Analysis Of Factors Affecting Employee Performance In Small Plantation Business (Case Study: Sumber Tani) - Ria Alisa Manulang; Aurik Gustomo (UniSadhuGuna Business School, 2024)
The agricultural sector, specifically the palm oil industry, is a significant contributor to Indonesia's GDP. South Sumatera is one of the largest producers of Indonesia's total palm oil production. The purpose of this study was to determine how the influence of Employee Motivation, Compensation, and Organizational Commitment on Employee Performance at Sumber Tani as one of smallholder plantations in South Sumatera, namely Sumber Tani. Sumber Tani experienced challenges related to employee performance which led to the non-achievement of harvesting targets and decline in sales. This research uses a quantitative approach with research methods, namely descriptive and verification analysis, data analysis is carried out by multiple regression analysis and importance performance analysis. The source of this research uses primary data with data collection using a questionnaire. The sample in this study were 41 workers at Sumber Tani using saturated sampling techniques. The results of descriptive analysis show that according to respondents's responses to Employee Motivation, Compensation, and Employee Performance at Sumber Tani are in the medium category and Organizational Commitment is in the high category. The results of hypothesis testing show that there is a positive and significant influence between Employee Performance, Compensation, and Organizational Commitment on Employee Performance, where these variables have an influence of 91.5% on Employee Performance. The results of importance performance analysis found that Compensation is the priority variable for improvement. Recommended strategies to improve Compensation at Sumber Tani are to conduct a salary survey, determine the amount of salary based on the salary survey, and provision of incentives.